Research of smart power station framework and practice of informatization construction - Xizhao WANG; Shengjun LIU; Dejun WANG; Ning HE (Dianxin kexue)
Based on the innovative development trend brought by industrial internet in America，industry 4.0 in Germany and integration of informatization and industrialization policy in China，from the perspective of power generation enterprise，the thinking of Guohua Power on the development of“three-in-one”construction framework of smart power station，and the detailed design scheme using“one control and three management”center，the“APS+field bus”digital technology application and“one body two wings three promotion”information construction as the core，were stated. Following this blueprint，program management approach was innovated，the problem that the implementation workis multiple，complex and strongly relevant was solved，initial results in six areas was achieved，the overall operation level of power plant was improved，and experience for the development of smart power industry in China was accumulated.